THE ROLE OF AI IN DIGITAL ERA - Surendra Sharma; Tiwari, Sanjay; Harsh Pareek; Devendra Kumar (International Journal of Psychosocial Rehabilitation, 2020)
This review paper looks with an overview of role of AI in education during the digital era. During the time of COVID-19 the usage of AI has increased rapidly. The paper helps us to highlights the benefits of AI in education sector like learning, teaching and ethical concerns associated with it.AI is a crucial factor in educational development and some threats are associated with it like safety, security and most important privacy. As a consequence, AI technologies positively and negatively affect the education sector.